Mapping landscapes in transformation : multidisciplinary methods for historical analysis (2019)
Innovation in mapping methods for historical landscape research is flourishing, largely because this type of research is situated at the very fertile intersection of ongoing technological development and sustained critical reflection. On the one hand, the development of digital tools for data capturing, data analysis and data structuring has revolutionised our ability to extract and plot out data of all sorts and to combine, mix and re-mix these data in order to discover spatio-temporal relationships that have previously remained hidden. On the other hand, the humanities’ sustained interest in spatiality as well as its growing involvement with the new digital tools make for a continuous critical reflection accompanied by ongoing methodological experiments that stretch, morph and bend these digital tools in order for them to reflect context and source specificity, to include different theoretical perspectives on landscape, to enable narrative formats, etc.